The influence of work environment on employees' work spirit study at PT. Ultimate Metal Mandala - Tita Rachtawati Santanu (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to determine the influence of the work environment on the work spirit of study employees at PT. ultimate metal mandala. The research methods used are descriptive and causal associative methods. Data collection techniques in this research are questionnaires, interviews, observation and literature study. Meanwhile, the data analysis techniques used are validity and reliability tests, Correlation Coefficient Test analysis, coefficient of determination and hypothesis testing. Based on the results of research by testing the correlation between Work Environment variables and Work Morale, a Spearman Rank correlation was obtained of 0.649. The correlation coefficient is in the